(untitled) (Research, Society and Development, 2022)
The objective was to analyze, in scientific productions, the process of validation of Educational Technology focused on the care of children and adolescents undergoing cancer treatment undergoing Hematopoietic Stem Cell Transplantation (HSCT) through an Integrative Review of the literature published between 2019 and 2021, with a search in Pubmed, Medline, CINAHL, Embase, BVS, and Web of Science databases, with descriptors established by MeSH and DeCS. Five articles were selected, international (60%) and national (40%), in English and Portuguese. The main results report that educational technologies can be used as a resource by the multidisciplinary team to assist in the care process, as it provides the patient and family with a channel for expressing their opinions and feelings. The review highlights the importance of searching for new technological tools that can favor a health education process. Thus, the validation process contributes to the recognition of such technologies by proving their effectiveness, in addition to indicating points to be improved to obtain better results and, therefore, allows the inclusion and strengthening of new teaching strategies.